Lipase‐Powered Mesoporous Silica Nanomotors for Triglyceride Degradation. (8th May 2019) - Wang, Lei; Hortelão, Ana C.; Huang, Xin; Sánchez, Samuel
Abstract: We report lipase‐based nanomotors that are capable of enhanced Brownian motion over long periods of time in triglyceride solution and of degrading triglyceride droplets that mimic "blood lipids". We achieved about 40 min of enhanced diffusion of lipase‐modified mesoporous silica nanoparticles (MSNPs) through a biocatalytic reaction between lipase and its corresponding water‐soluble oil substrate (triacetin) as fuel, which resulted in an enhanced diffusion coefficient (ca. 50 % increase) at low triacetin concentration (<10 mm ). Lipase not only serves as the power engine but also as a highly efficient cleaner for the triglyceride droplets (e.g., tributyrin) in PBS solution, which could yield potential biomedical applications, for example, for dealing with diseases related to the accumulation of triglycerides, or for environmental remediation, for example, for the degradation of oil spills. Abstract : Lipase‐basierte Nanomotoren zeigen in Triglycerid‐Lösung über lange Zeiträume verstärkte Brownsche Bewegung und bauen Triglycerid‐Tröpfchen ab. Die biokatalytische Reaktion zwischen der Lipase und ihrem wasserlöslichen Ölsubstrat Triacetin als Kraftstoff führt zu einer erhöhten Diffusion der Lipase‐modifizierten mesoporösen Siliciumdioxid‐Nanopartikel für ca. 40 min.